Ukrainian civil society institutions and organisations activities under special legal regimes - V. V. Pylyp (Law and Safety)
The activity of state institutions and civil society under special legal regimes differs from the general procedure for exercising their powers to some extent. This is due to both the conditions in which they operate and the regulatory and legal changes that are mainly aimed at regulating social relations in accordance with the realities of public life. Given the above, the purpose of the study was to determine the peculiarities of the activities of institutions and organisations of civil society in Ukraine under emergency legal regimes, in particular during martial law and the state of emergency.